Estimation of nonlinear models with mismeasured regressors using marginal information - Yingyao Hu; Geert Ridder (The Johns Hopkins University, Department of Economics, 2009)
We consider the estimation of nonlinear models with mismeasured explanatory variables, when information on the marginal distribution of the true values of these variables is available. We derive a semi-parametric MLE that is shown to be consistent and asymptotically normally distributed. In a simulation experiment we find that the finite sample distribution of the estimator is close to the asymptotic approximation. The semi-parametric MLE is applied to a duration model for AFDC welfare spells with misreported welfare benefits. The marginal distribution of the correctly measured welfare benefits is obtained from an administrative source.
Keywords: C14; C41; I38; 330; Measurement error model; marginal information; deconvolution; Fourier transform; duration model; welfare spells